Self-Reflection Model Based on Fact, Feeling, Finding, Future, Framework to Produce Reflective Teachers in Elementary Schools - Faisal; Sembiring, Masta Marselina; Lova, Stelly Martha; Ladin, Che Aleha Binti; Mariana, Neni (JTP - Jurnal Teknologi Pendidikan, 2025)
This study aims to explore the application of the 5F-based Self-Reflection model (Fact, Feeling, Finding, Future, Framework) in improving the reflective ability of pre-service teachers in elementary schools. This model is designed to assist pre-service teachers in evaluating and improving their teaching practices through structured reflection. This study uses the Collaborative Nested Action Research (C-NAR) approach by involving 20 pre-service teacher students during teaching practice at partner schools. Data were collected through questionnaires, observations, and documentation to assess the impact of these models on the development of their reflective abilities. The results show that the 5F-based Self-reflection model significantly helps pre-service teachers in improving the quality of teaching and classroom dynamics. Through reflection, teachers can identify learning challenges, design more innovative teaching strategies, and plan improvements for the future. This model has proven to be effective in improving student engagement, better time management, and a deeper understanding of the material. This research contributes to the development of a structured reflection model for teacher education. These findings show that the application of this model can significantly improve the competence of pre-service teachers. Further research is needed to explore the long-term impact of this model and its application to other educational contexts.